THE ROLE OF MOBILE PHONE AND POWERPOINT IN ENHANCING WRITING SKILLS: LECTURERS’ REFLECTIONS - Muhammad Siddique; Manvender Kaur Sarjit Singh (Proceedings of The ICECRS, 2016)
These day mobile phones are being resorted to as indispensable pedagogical tools for imparting language skills to the present day students who are termed as ‘Generation Y’, ‘Net Generation’ and above all ‘Digital Natives’. Mobile phones have the potential to be reliable pedagogical tool to teach writing which is the most neglected skills to the intermediate students. The current paper examines the perceptions of two lecturers regarding the use of mobile phones and PowerPoint in teaching descriptive essay writing skills to intermediate students at M.A.O. College, Lahore. The qualitative data for this purpose was collected by means of semi-structured interviews from those two lecturers who taught experimental as well as control groups respectively. The findings of the study indicated that the lecturer of experimental group was very much in favour of mobile phones to be incorporated in the teaching writing class. Even the lecturer of control group favoured the use of new technology as she was not in favour of PowerPoint to be used for teaching writing skills. Moreover, the findings of the study indicated that the mobile phones can very easily, successfully and conveniently be employed as pedagogical tool to impart writing skills as they can motivate the lecturers for teaching as well as the students for learning the writing skills.